Predictive factors of disability in patients with leprosy - Gonçalves, Soraya Diniz (2009)
OBJECTIVE:To analyze predictive factors in the progression of the disability grade in patients with leprosy. METHODS: A retrospective cohort study followed up 595 patients with disability registered at a healthcare unit in the city of Belo Horizonte (Southeastern Brazil) from 1993 to 2003. Patients' sociodemographic and clinical information was collected from the respective medical records. Comparisons were made between the disability grade upon admission and at the end of treatment using a marginal homogeneity test. To determine factors associated with progression in the disability grade, univariate analysis (linear trend chi-square test) was employed, as well as multivariate analysis by means of the algorithm Chi-square Automatic Interaction Detector. RESULTS:Among the cases in which the disability grade was recorded upon admission and upon discharge, 43.2% of the patients who had grade 1 in the first assessment progressed to grade 0. Among those who began with grade 2, 21.3% progressed to grade 0 and 20% progressed to grade 1. In the univariate analysis, the variables that proved to be statistically associated with progression in the disability grade were: neuritis, time elapsed until the occurrence of neuritis, number of damaged nerves, type of physiotherapy treatment and higher dose of prednisone. In the multivariate analysis, the main factor associated with the progression of disability was the disability grade upon admission. CONCLUSIONS: The results showed the importance of an early diagnosis of neuropathy as well as the efficient association of pharmacological and non-pharmacological treatment, through disability prevention techniques and adequate doses of steroid.